PEMBENTUKAN KARAKTER PELAUT MELALUI PENDEKATAN KONSEPTUAL “Co-PROL” - Wegig Pratama (Sekolah Tinggi Maritim Yogyakarta, 2015)
The opportunity to fill the high demand for international seaferers has not been met due to the mismatch between the requirements and education outcomes. In addition to the required knowledge and skill, personal character of the gradutes must also been built. Such personal character building is a crucial aspect to be a serious concern of Higher Degree Seaferer Education Institutions. The implementation of character building can not be separated from other aspects, but it should be considered in an assimilative manner. From the teaching-learning point of view, character building can be carried out through the combination of Cooperative Learning and Problem-Based Learning, that is being called as Co-PROL by the author. The Co-PROL is conceptually a teaching-learning approach that fit such requirement because it accommodate the two theories that is inline with the teaching outcomes by combining behavioristic and constructivistic learning theories.